Genome-wide analysis of basic helix–loop–helix genes in Dendrobium catenatum and functional characterization of DcMYC2 in jasmonate-mediated immunity to Sclerotium delphinii - Li, Cong; Cai, Xiang; Shen, Qiuyi; Chen, Xueliang; Xu, Mengxi; Ye, Tianqi; Si, Dun; Wu, Lingshang; Chen, Donghong; Han, Zhigang; Si, Jinping (Frontiers in Plant Science, 2022)
Dendrobium catenatum, belonging to the Orchidaceae, is a precious Chinese herbal medicine. Sclerotium delphinii (P1) is a broad-spectrum fungal disease, which causes widespread loss in the near-wild cultivation of D. catenatum. Thus, D. catenatum resistance breeding has become the key to solve this problem. The bHLH gene family is closely related to plant resistance to external stresses, but the related research in D. catenatum is not deep enough yet. Phylogenetic analysis showed that 108 DcbHLH genes could be divided into 23 subgroups. Promoter cis-acting elements revealed that DcbHLHs contain a large number of stress-related cis-acting elements. Transcriptome analysis of MeJA and P1 treatment manifested that exogenous MeJA can change the expression pattern of most bHLH genes, especially the Ⅲ e subgroup, including inhibiting the expression of DcbHLH026 (MYC2a) and promoting the expression of DcbHLH027 (MYC2b). Subcellular localization indicated that they were located in the nucleus. Furthermore, exogenous MeJA treatment significantly delayed disease time and reduced lesion size after infection with P1. DcMYC2b-overexpression Arabidopsis lines showed significantly smaller lesions after infected with P1 than the wild type, indicating that DcMYC2b functions as an important positive regulator in D. catenatum defense against P1. Our findings shed more insights into the critical role of DcbHLH family in plants and in the resistance breeding of D. catenatum.